2017
DOI: 10.3389/fimmu.2017.00760
|View full text |Cite
|
Sign up to set email alerts
|

NK Cell Exhaustion

Abstract: Natural killer cells are important effector lymphocytes of the innate immune system, playing critical roles in antitumor and anti-infection host defense. Tumor progression or chronic infections, however, usually leads to exhaustion of NK cells, thus limiting the antitumor/infection potential of NK cells. In many tumors or chronic infections, multiple mechanisms might contribute to the exhaustion of NK cells, such as dysregulated NK cell receptors signaling, as well as suppressive effects by regulatory cells or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
239
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 252 publications
(249 citation statements)
references
References 125 publications
9
239
0
1
Order By: Relevance
“…Therapeutic targeting of these immune checkpoint receptors is rapidly growing in cancer therapeutic strategies [46]. Similarly to T cells, NK cell exhaustion has also been described in numerous cancers and chronic viral infections [47, 48]. McWilliams et al[49] showed that therapeutic blockade of CD94/NKG2A, defined as an inhibitory signaling receptor, can restore the functional activities of NK cells in CLL patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic targeting of these immune checkpoint receptors is rapidly growing in cancer therapeutic strategies [46]. Similarly to T cells, NK cell exhaustion has also been described in numerous cancers and chronic viral infections [47, 48]. McWilliams et al[49] showed that therapeutic blockade of CD94/NKG2A, defined as an inhibitory signaling receptor, can restore the functional activities of NK cells in CLL patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our current study only includes hospitalized RSV patients, and compares those on the wards (Moderate) and and various mechanisms of programmed cell death have been delineated (36). During chronic viral infections CD8+ T-cell exhaustion occurs (34), viral nucleotide analogues cause dendritic cell necroptosis (37), and influenza A (H1N1) induces PDL1 on human T-cells and dendritic cell (38), while NK cell exhaustion is also described in viral infections (39).…”
Section: Discussionmentioning
confidence: 99%
“…A clear phenomenon of induction of CRTAM expression and TGF‐β production was observed and, of high interest, PD‐1 and PD‐L1 were up‐regulated (Fig. A), similar to that of exhausted phenotypes in this and other effector populations of the immune system . Analyses at 12 or 120 h of subfractionated CD56 hi and CD56 dim NK subsets indicated that CD56 hi regulatory cells are able to become exhausted‐like cells endowed with suppressor long‐lasting properties (Fig.…”
Section: Resultsmentioning
confidence: 72%
“…Of note, the notion of cell exhaustion in immunological surveillance cellular populations has gained substantial importance in the biology of cancer, due to its potential function in the transition from the elimination to the escape stages of the cancer immunoedition process. As a result of active mechanisms and abnormal microenviroments, exhaustion of NK cell functions is exhibited in tumors, including Kaposi sarcoma, renal cell carcinoma, multiple myeloma, and lung, liver, ovarian, and breast cancer, displaying poor effector functions and altered phenotypes . Finally, in response to human leukocyte dialyzate extracts, stem and progenitor cells contribute to the emergent production of a special subgroup of CD11c + NK cells endowed with abilities of IFN‐γ production, cytotoxicity of tumor cells, and proliferation of Tγδ lymphocytes induction …”
Section: Introductionmentioning
confidence: 99%